The effectiveness of combination of massage therapy and heat therapy towards reducing pain and increasing range of motion (rom) knee injury - Cerika Rismayanthi; Diki Triyudi Refindo (Jorpres (Jurnal Olahraga Prestasi), 2023)
Knee injuries are common in both the general public and sportsmen. This study aims to examine the effectiveness of the combination of massage therapy and heat therapy on reducing pain and increasing range of motion (ROM) of the knee joint after knee injury. This study used a pre-experimental design with a one group pretest - posttest design. The population in this study were patients with knee injuries who came to the Clinic for Sports Injury Therapy and Fitness. The sampling technique used purposive sampling with a span of 1 month and obtained a sample of 24 people. Subjects received massage therapy treatment which was carried out for 20 minutes, followed by heat therapy for 10 minutes. The instrument used to measure the pain scale was using the Numeric Rating Scale (NRS) and the joint space or Range of Motion (ROM) using goniometry. The data analysis technique used quantitative descriptive, hypothesis testing using the Wilcoxon signed rank test to test data that were not normally distributed with a significance level of 5%. The results of the data analysis showed the Wilcoxon signed rank test analysis showed the pretest flexion ROM value experienced by the subject was 110.0 - 139.0 with an average of 129.8 and a standard deviation of 7.22. While the posttest Flexion ROM value experienced by the subject with an average of 135.4 and a standard deviation of 4.15. The standardised Z value is -4.118 (based on negative rank) with a significance value of 0.000. The pretest extension ROM experienced by the subjects was 0 - 25 with a mean of 5.95 and a standard deviation of 5.27. While the posttest extension experienced by the subject with an average of 1.95 and a standard deviation of 1.82. The standardised Z value was -3.778 (based on negative rank), with a significance value of 0.000. Based on the results of the research that has been obtained, it can be concluded that the combination of massage and heat therapy can effectively reduce pain significantly (p 0.05), with the effectiveness of reducing flexion pain by 51.87%, decreasing extension pain by 53% and increasing ROM. significantly (p 0.05), with the effectiveness of increasing flexion ROM by 4.9%, increasing extension ROM by 67%.